Systematic review of randomized control trials into effective preoperative weight loss interventions and impact on surgical outcomes for major benign gynecological surgery. Issue 8 (22nd April 2022) - Atkinson, Andrea; Pass, Glenn; Megaw, Lauren
Abstract: Aims: Limited information exists on what preoperative weight loss interventions (lifestyle, pharmacological, surgical) are effective in improving outcomes of elective, nononcological, gynecological surgery. Obesity rates are increasing and associated with poorer operative outcomes. We aimed to identify high quality studies into preoperative weight loss interventions and perform a systematic review of the literature to guide recommendations for reducing gynecological surgical complications and guide future research. Primary outcomes were mortality and surgical complications including conversion to open surgery, duration of surgery, and recovery. Methods: The review was pre‐registered with PROPSERO. A systematic search was undertaken of the major electronic bibliographic databases. Search results were compiled and abstracts of studies identified before application of the Cochrane highly sensitive search strategy (CHSSS) were reviewed. Full text of studies after application of the CHSSS were evaluated for suitability. For data collection and analysis, a minimum three high‐quality randomized control trials were required to synthesize data in relation to the primary outcome. Results: No trials met the inclusion criteria. No randomized control trials in gynecological cohorts were identified. Studies in gynecology‐oncology were excluded due to the confounding nature of weight loss as a feature of illness as opposed to health optimization. Conclusion: There is limited evidence regarding preoperative weight loss interventions in gynecology. Further research is needed as the prevalence of obesity among women is increasing and definitive surgical management options in gynecology remain essential. PROSPERO registration ID: 165643.